Public-Private Employment Choice, Wage Differentials and Gender in Turkey - Aysit Tansel (Institute for the Study of Labor (IZA), 2004)
The main objective of this paper is to examine the factors which explain the employment choice and the wage differentials in the public administration, state owned enterprises and the formal private wage sector in Turkey. Selectivity corrected wage equations are estimated for each sector for men and women separately. Oaxaca-Blinder decomposition of the wage differentials between sectors by gender and between men and women by sector are carried out. Results indicate that when controlled for observed characteristics and sample selection, for men, public administration wages are higher than private sector wages except at the university level where the wages are at par. State owned enterprise wages for men are higher than private sector wages. Similar results are obtained for women. Further, while wages of men and women are at parity in the public administration, there is a large gender wage-gap in the private sector in favor of men. Private returns to schooling are found to be lower in the noncompetitive public rather than in the competitive private sector.
Keywords: J16; J31; J45; 330; public-private wages; gender; Turkey; Lohnstruktur; Privatwirtschaft; Öffentliche Verwaltung; Öffentliches Unternehmen; Lohndifferenzierung; Geschlecht; Türkei